Unravelling the foci of employee commitment. Issue 1 (13th March 2017) - Cafferkey, Kenneth; Harney, Brian; Dundon, Tony; Edgar, Fiona
Abstract : Purpose: The purpose of this paper is to extend understanding regarding the basis and foci of employee commitment. It does so by exploring the direction towards employee centric rather than an assumed organisation basis of commitment. Design/methodology/approach: Survey data of over 300 employees from a variety of organisations in the Republic of Ireland were collected. Data focussed on worker orientations and their foci of commitment. Findings: The findings confirm a more pluralistic and mixed basis to the antecedents of worker commitment, as opposed to an assumed human resource management unitarist ideology often promoted by organisational managers. At the level of individual workers, a dominant focus for commitment relates to career development and the milieu of an immediate workgroup. Practical implications: There are three implications. First, mutual gains possibilities are not straightforward and there are practical pitfalls that employee interests may get squeezed should managerial and customer interests take precedence. Second, there remain competing elements between job security, flexibility and autonomy which can impact performance. Finally, line managers are key conduits shaping commitment and especially psychological contract outcomes. Originality/value: This paper unpacks the relationship between ideological orientation and an individual's foci of commitment. The research found that traditional orientations and foci of commitment are deficient and that simplified individualistic interpretations of the employment relationship are complex and require more critical scrutiny.